Pluralism and the pragmatic turn : the transformation of critical theory : essays in honor of Thomas McCarthy - McCarthy, Thomas A.; Rehg, William; Bohman, James (Cambridge, Mass. : MIT Press, 2001)
The essays in this volume reflect on and expand Frankfurt School critical theory as reformulated after World War II by Karl-Otto Apel, Jurgen Habermas, and others. Frankfurt School critical theory since the pragmatic turn has become a richer source of critical analysis that is at the same time socially and politically more effective. The essays are dedicated to Thomas McCarthy, who has done perhaps more than any other scholar to introduce English-speaking audiences to contemporary German critical theory. The book is organized into three parts. Part one deals with social theory and the rational basis of communication, including basic issues raised by the pragmatic turn. Part two examines conceptions of autonomy and the self. Part three deals with political theory, focusing on problems stemming from sociocultural pluralism. Together, the essays provide an overview of the latest developments in Frankfurt School critical theory as it responds to the challenges of pragmatism and social pluralism.
From Kant's "ideas" of pure reason to the "idealizing" presuppositions of communicative action: reflections on the detranscendentalized "use of reason"/ Jürgen Habermas -- The ambiguity of "rationality" / Richard Rorty -- Practical reason, the "space of reasons," and public reason / Kenneth Baynes -- Participants, observers, and critics: practical knowledge, social perspectives and critical pluralism / James Bohman -- Adjusting the pragmatic turn: ethnomethodology and critical argumentation theory / William Rehg -- Do social philosophers need a theory of meaning? Social theory and semantics after the pragmatic turn / Barbara Fultner -- Problems in the theory of ideology / Joseph Heath -- Competent need-interpretation and discourse ethics / Joel Anderson -- Into the sunlight: a pragmatic account of the self / M. Johanna Meehan -- Mutual recognition and the work of the negative / Joel Whitebook -- Taking ethical debate seriously / Georgia Warnke -- The logic of fanaticism: Dewey's archaeology of the German mentality / Axel Honneth -- Political pluralism in Hegel and Rawls / Andrew Buchwalter -- Of guests, aliens, and citizens: rereading Kant's cosmopolitan right / Seyla Benhabib -- Beyond liberalism: toleration and the global society in Rawls's Law of peoples / David M. Rasmussen.
Includes bibliographical references (pages 431-435) and index.
Print version record.
eBooks on EBSCOhost
Keywords: McCarthy, Thomas A; McCarthy, Thomas A; McCarthy, Thomas, -- 1940-; McCarthy, Thomas, -- 1940-; Frankfurt school of sociology; Critical theory; Cultural pluralism; Pragmatism; École de Francfort (Sociologie); Théorie critique; Diversité culturelle; Pragmatisme; critical theories (dialectical critiques); pragmatism; critical theory (sociological concept); SOCIAL SCIENCE -- Regional Studies; SOCIAL SCIENCE -- Anthropology -- General; Critical theory; Cultural pluralism; Frankfurt school of sociology; Pragmatism; Kritische Theorie; Critical theory; Cultural pluralism; Pragmatism; PHILOSOPHY/General; CULTURAL STUDIES/Critical Theory; Festschriften; Festschriften